RESORPTION OF MULTIPLE FETUSES AT MID~GESTATION IN A BITCH - SINGLA, V K; VARUGHESE, EMY E; R, UPASANA; BHAT, G R; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
A rare case of fetal resorption of multiple fetuses in a pregnant bitch due to bacterial infection is described.
Keywords: Bitch; Resorption; Pregnancy; Fetus